Hassan Hanafi and Islamic Legal Theory: (Mazahib, 2021)
Islamic legal theory (popularly known as uṣū al-fiqh in Islamic term) runs into difficulties when dealing with social and humanities issues. Religious texts, according to Hassan Hanafi’s perspective, should not only be positioned as a source of law, but also at the same time must be seen as a phenomenological experiences of religiosity. The dialectic of religious text and today's empirical context needs to be reformulated. By using phenomenological as a methodological tool, Hassan Hanafi makes an effort of reepistemification of uṣū al-fiqh reason into three typologies of consciousness; historical, eidetic, and praxis. These three aspects constitute the discursive relationship to present an anthropocentric dimension in uṣū al-fiqh reason. This article uses qualitative research methods with interpretation criticism approach. This article aims to analyze the new formula offered by Hassan Hanafi’s uṣū al-fiqh reason, and to examine it to criticize the slogan “Back to the Qur'an and Sunna” as a phenomenon of religiosity. Keywords: Uṣū al-fiqh, Hassan Hanafi, Phenomenology, Back to the Qur’an and Sunna